Association of clinical manifestations, disease activity, and medications on premature atherosclerosis in systemic lupus erythematosus - Pratama, Mirza Zaka; Kusworini Handono; Cesarius Singgih Wahono; Ahmad Bayhaqi Nasir Aslam; Syahrul Chilmi (Heart Science Journal, 2025)
Background SLE is distinguished by the development of multiple autoantibodies that lead to chronic inflammation and increased risk of cardiovascular diseases, especially atherosclerosis. Objective This examination sought to explore the association between the disease activity, clinical manifestations, and medication with the atherosclerotic lesion from SLE patients. Methods This inquiry investigated forty-two female SLE patients (18-45 years old) who met the 2019 EULAR/ACR assortment decency with matched healthy individuals as control A cross-sectional study was sanctioned at the Rheumatology Clinic of Saiful Anwar General Hospital Malang between July and November 2023. Demographic data, clinical manifestations, and medication history was documented in the medical records. Disease activity was stelled by the SLEDAI-2K score. Carotid Intima-Media Thickness (cIMT) and Flow-Mediated Dilation (FMD) (after brachial BP cuff inflation up to 200 mmHg for five minutes) examinations were used as atherosclerosis marker. Results Markedly higher of cIMT mean was demonstrated in SLE patients compared to healthy individual (0.51±0.11 vs 0.40±0.11 mm, p<0.001). FMD was subtancially curtailed in SLE patients set side to side to control (0.00 (0.00-0.10) vs 0.10 (0.00-0.28) mm, p=0.022). There was no statistical distinctness of the cIMT and FMD among SLE patients according to the presence of clinical manifestations. Neither cIMT nor FMD showed a statistically correlated with the disease activity. Patients who received hydroxychloroquine (0.57±0.02 vs. 0.50±0.09 mm, p=0.043) and cyclophosphamide (0.55±0.09 vs. 0.48 ± 0.10 mm, p=0.031) had higher cIMT. Higher cIMT was demonstrated in subjects who received steroid (p=0.045) and the dosage of steroid was essentially enforced to cIMT (R=0.418, p=0.034). Conclusion Our study unveil that early atherosclerosis was evidenced in patients with SLE and several medications might affect the progressivity of atherosclerosis.